Como o Sharding no MongoDB pode impactar na escalabilidade do banco de dados MongoDB. - SANCHEZ, Pedro Bernardo (2023)
As millions of data are generated every day all over the world, increasingly integrated and capable databases are needed to manage all this information. It consists of improving the hardware's capacity for horizontal scalability, which consists of distributing the work required to perform operations among several servers. One of the main databases used in the creation of scalable applications is MongoDB, which is a document-oriented non-relational database, and it is possible to implement a sharding technique, which directly impacts the performance of the database and also in the cost necessary to maintain it. The main objective and motivation for this research was to present the impacts caused in performance and cost when implementing sharding in a MongoDB database.